Wilson Disease. Issue 4 (August 2016) - Pfeiffer, Ronald F.
Abstract : ABSTRACT: Purpose of Review: This article reviews the clinical features of Wilson disease, focusing on the neurologic and psychiatric abnormalities, and addresses the diagnostic workup and treatment approaches to managing the disease. Recent Findings: The list of known mutations causing Wilson disease continues to grow, but advances in genetic testing may soon make it feasible to routinely perform genetic testing on individuals suspected of having Wilson disease. Summary: Wilson disease is a rare genetic disorder with protean manifestations that should be considered in the differential diagnosis of any individual presenting with unexplained neurologic, psychiatric, or hepatic dysfunction. Appropriate diagnostic testing should be expeditiously performed and treatment promptly initiated and maintained since failure to diagnose and treat Wilson disease will result in progressive and ultimately irreversible damage to the neurologic and other systems.